Impact of night shifts on laparoscopic skills and cognitive function among gynecologists. (30th September 2014) - Veddeng, Anne; Husby, Thomas; Engelsen, Ingeborg B.; Kent, Andrew; Flaatten, Hans
Abstract Objective To assess whether gynecologists have impaired laparoscopic skills and/or reduced cognitive function after long on‐call hours. Design Prospective cohort study. Setting Department of Gynecology and Obstetrics, Norway. Population 28 gynecologists working long shifts in a single department. Methods Pre‐training of laparoscopic skills on a virtual reality simulator. Simulator‐ and cognitive testing on two different occasions; one in the morning after a normal nights' sleep at home and one in the morning directly after 17.5 h on call. The virtual reality simulator test consisted of three repetitive salpingectomies in an ectopic pregnancy module. The cognitive test consisted of a standardized cognitive test battery (Cambridge neuropsychological test automated battery). Main outcome measures Simulated laparoscopic performance was assessed by time to perform the procedure, total length of instrument movement (tip trajectory) and blood loss. Cognitive function was assessed by reaction time, errors and total score. Results No significant impairment in laparoscopic skills was found after 17.5 h on call. Cognitive testing revealed a statistically significant increase in reaction time post‐call. Construct validity for the metrics "time to perform procedure" and "tip trajectory" in the ectopic pregnancy module was established in a validation study prior to our main study. Conclusions We were not able to detect impaired laparoscopic skills among gynecologists tested by a virtual reality procedural module after 17.5 h on call. We found a small increase in reaction time but no other signs of reduced cognitive function. The study adds information on surgical performance of sleep‐deprived gynecologists.